Reactivity of the triple task on writing processes and product in adults with dyslexia - Olujić Tomazin, Marina; Kuvač Kraljević, Jelena; Alves, Rui A. (Frontiers in Psychology, 2023)
Introduction The triple task (TT) is a method for assessing the dynamics of writing processes. It involves three tasks in one: writing a text, responding to a sound, and reporting the process. Previous research has mostly shown that the TT does not affect the writing process or the product. However, individuals with dyslexia often show difficulties in tasks that require organization, automation, integration of multiple processes, inhibition, and shifting/cognitive flexibility. The aim of this study was therefore to investigate whether TT affects the writing process and written product differently in adults with dyslexia compared to a control group of adults with typical reading skills. Methods Two groups of adult native Croatian speakers were included in this study: 20 adults with developmental dyslexia and 20 adults with typical reading skills; evenly distributed by: age (18–38 years), gender (13 males, 7 females per group), educational level, and nonverbal cognitive abilities. All participants wrote one text with a TT and another without. The writing of the text was tracked with a keystroke logging program – Inputlog. The two texts were compared at process and product level. Results and discussion The results showed that measures of writing processes and text quality in the groups of adults with dyslexia and adults with typical reading skills were unlikely to be differentially affected by TT. However, in the condition without TT, the total number of characters per minute was higher, more keys were typed per minute and more words were deleted. As expected, adults with dyslexia produced shorter texts of lower quality and with more errors; they also produced fewer characters per minute, used fewer keystrokes and typed fewer. Conclusion The study suggests that TT is unlikely to have a different impact on the writing process or written product in adults with dyslexia compared to adults with typical reading skills.